Optimizing care of breast cancer patients from low resource countries who immigrate to New York City: A case series from a large public hospital. Issue 11 (20th September 2020) - Crown, Angelena; Choi, Jee‐Hye; Cole‐Price, Ayana; Horowitz, Elizabeth; Joseph, Kathie‐Ann
Abstract: Global disparities in breast cancer care become particularly evident when patients seek definitive care in the United States (USA) after receiving a breast cancer diagnosis and initiating care in low‐ and middle‐income countries (LMICs). We performed a retrospective review of 26 patients with breast cancer who immigrated from LMICs and received care at Bellevue Hospital. Fifteen (58%) presented with advanced disease (stage III or IV), including 7 (27%). All 26 patients required diagnostic work‐up in the USA, and all 19 (73.1%) patients with stage 0‐III disease underwent surgical excision. Patients from LMICs frequently present with advanced disease and in varying stages of breast cancer treatment. Improving communication with previous providers and fostering a collaborative approach with the international community are essential to developing efficacious treatment plans and improving oncologic outcomes.